Effect of intra-organisational competition on organisational performance indicators - Chauhan, Harsh; Kalkis, Henrijs (University of Latvia, 2021)
The objective of the research is to investigate intra-organisational competition (IOC) emerging from the interactions of internal social comparison (ISC) and intra-organisational evolution (IOE) effecting organisational performance (OP). Communication between subordinates, comparing contribution, ability to perform and business management strategies resulting in IOC. The attention is on recognised social dimensions and equal emphasis is on business management practices. The literature attempts’ to recognise ISC and IOE and its effect on OP balances the conceptual paper. For the purpose Google Scholar, Emerald Insight, EBSCO Host and Science Direct database has been used. Literature relies on human tendency to compare and coordinate work activities. It identifies the response towards comparison and pressure created within work environment affecting employees ability to operate and function efficiently. The concentration is on business process and employee’s irrational behaviour affecting individual performance. The study assesses consequences of IOC on employees followed by its outcome on organisation’s performance. The application is on variables (ISC, IOE & OP) and critical factors that affects work environment due to intra-organisational strategy of competitive behaviour implemented by employers’ in encouraging “Intra-organizational competition”.
Keywords: Intra-organisational; Competition; Internal Social Comparison; Evolution; Performance; Research Subject Categories::SOCIAL SCIENCES::Business and economics